CORPORATE GOVERNANCE AND FINANCIAL STATEMENT FRAUD IN INDONESIA’S FINANCIAL INDUSTRY: THE CRIME MODEL APPROACH - Pertiwi, Ananda Marisa; Arum, Enggar Diah Puspa; Brilliant, Aulia Beatrice (Journal of Business Studies and Management Review, 2026)
Corporate governance plays a strategic role in mitigating fraud by strengthening oversight functions, enhancing managerial transparency and accountability, and optimizing internal control systems in financial reporting. This study aims to examine and analyze the role of corporate governance in detecting financial statement fraud using the CRIME Model, which measures fraud motivation from five aspects: cooks, recipes, incentives, monitoring, and end results. The study was conducted on financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2025. The data used in this study consisted of 360 sets of secondary data obtained from company financial reports. The analysis used to test the research hypothesis was Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that the aspects of cooks and end results had a significant impact on detecting financial statement fraud. Meanwhile, others, such as recipes, incentives, and monitoring, had no impact on detecting financial statement fraud.